The Importance of Innovative Leadership in Improving Organisational Readiness for Technology Disruption - Sunarmo Sunarmo; Puspa Rini; Diah Nurdiana; Nicko Albart; Siti Hasanah (Jurnal Minfo Polgan, 2023)
The rapid development of technology has led to disruption in various industries and sectors. Technological disruption refers to a fundamental change in the way businesses and organisations operate due to the adoption of new technologies that change traditional business models. This research aims to illustrate the importance of innovative leadership in improving organisational readiness in the face of technological disruption. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results show that innovative leadership plays a very important role in improving organisational readiness to face technological disruption. Technological disruption has fundamentally changed the business landscape, and organisations need to adopt innovative approaches to remain relevant, competitive and sustainable in this dynamic environment. Innovative leadership helps organisations understand the impact of technology, deal with the changing business environment, and improve competitiveness by creating competitive advantage through innovation.